Chronic Bacterial Prostatitis due to Staphylococcus haemolyticus; Case Report - Sholeh Ebrahimpour; Sirous Jafari (Research Center for Rational Use of Drugs (RCRUD), 2018)
Prostatitis causes up to 25% of male genitourinary complaint. However, due to technical restrictions in sampling, only in 10% of cases pathogens were identified. In this paper, a patient with chronic prostatitis due to Staphylococcus hemolyticus is described. A 48-year-old man was referred with longstanding (approximately for 18 months) complaint of increased genitourinary symptoms and pain in perineum. In evaluation, moderate growth of methicillin-resistant Staphylococcus hemolyticus (MRSH) in post-prostatic massage voided urine and expressed prostatic secretion (EPS) was positive. Culture of urethral urine (urine or voided bladder 1; VB1), midstream urine (VB2) and post-ejaculation urine specimens were negative. Leukocyte count values in EPS and post-prostatic massage voided urine were 14 and 8 per oil immersion field respectively. PCR of urine samples was positive for Ureaplasma urealyticum and confirmed by repeated analysis. Based on the antimicrobial susceptibility results patient was treated with teicoplanin 400 mg intramuscularly every 12 hours for three doses followed by the daily maintenance dose of 400 mg.  In addition, doxycycline 100 mg twice daily was added to cover Ureaplasma urealyticum. Treatment course completed in 6 weeks. Alleviation of patient's symptoms begun within the first week of treatment and this trend continued until the end of the treatment.